Synthesis of carbon nanotube and nanoclay composites of polyanthranilic acid and their effects on electronic properties - Singh A.K.; Prakash R. (My University, 2025)
Multiwalled carbon nanotubes (MWNTs) are considered as promising candidates for electronic devices due to their unique electrical and mechanical properties combined with chemical stability. The synthesis and characterizations of PANA-MWNTs and PANA-Clay nanocomposites prepared by in situ polymerization are reported. The current density-voltage (J-V ) characteristics of these devices shows the rectifying contact with Al metal, however, with significant variation in performance parameters like barrier height, ideality factor and reverse saturation current. Nanocomposites showed a significant improvement in their electronic properties and potential for device applications. Copyright © 2011 American Scientific Publishers All rights reserved.